Analisis Tingkat Kepuasan dan Pengalaman Pengguna Aplikasi Bappedasmartservice Menggunakan Metode SUS - Yahya Rizki Imansyah; Noordin Asnawi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study aims to analyze the level of satisfaction and user experience of the Bappedasmartservice application at the Madiun Regency Public Order Agency (Satpol PP) and Fire Department. The System Usability Scale (SUS) method was used, using a quantitative descriptive approach through observation and questionnaires distributed to six active users of the application. The measurement results showed an average SUS score of 73.3, which falls into the "Good" category, indicating that the application has a good level of usability and is acceptable to users. However, several aspects still need improvement, particularly access speed, system stability, and data security, so that the application can provide a more optimal user experience and support the effective and efficient digitalization of government services.